PERUBAHAN GAYA PAKAIAN PEREMPUAN BANGSAWAN PRIBUMI DI JAWA TAHUN 1900 - 1942 - Ayu Septiani (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2015)
The title of this article is Change of Nob Indigenous Women’s Fashion Mode in Java, 1900-1942. This article discusse the lifestyle change consisting of thoughts, behaviors, and performance of nob indigenous women in Java, 1900-1942. There are the three aspects of change of nob indigenous women lifestyle.. Education and interaction with European women are the main factors causing the change. Meanwhile, Javanese customs that govern all aspects of the nob indigenous women's lives become the background of this study. Research method applied is historical method having four stages of work, namely heuristic, criticism, interpretation, and historiography.